Palliative Radiation Therapy for Vertebral Metastases and Metastatic Cord Compression in Patients Treated With Anti-PD-1 Therapy - Fareed, Muhammad Mohsin; Pike, Luke R. G.; Bang, Andrew; Huynh, Mai Anh; Taylor, Allison; Spektor, Alexander; Awad, Mark M.; Ott, Patrick A.; Krishnan, Monica; Balboni, Tracy A.; Schoenfeld, Jonathan D. (Frontiers in Oncology, 2019)
Background:There is increasing use of immune checkpoint blockade (ICB) across multiple cancer types,including in patients at risk for vertebral metastases and cord compression.These patients are often treated with palliative radiotherapy(PRT);however,data evaluating the combination of PRT and ICB in patients with vertebral metastases is limited. Furthermore, patients with cord compression are generally excluded from prospective clinical trials. Therefore, we retrospectively evaluated outcomes following PRT and PD-1 inhibition in patients with vertebral metastases. Methods:We performed a retrospective chart review of 37 consecutive patients (total 57 lesions) treated with radiation for vertebral metastases who also received PD-1 inhibition. Patient,treatment and outcomes data were abstracted from the medical records. Results:Histologies included non-small cell lung cancer(n=21),renal cell carcinoma(n= 9) and melanoma(n=7). Out of 57 lesions,18 involved >1 segments of the vertebral column. There were isolated lesions in thoracic(16),lumbar(9),cervical(6)and sacral(8)vertebrae.Presenting symptoms included pain(19),numbness(10)and weakness(3).Eleven patients were asymptomatic.Radiologic cord compression was present in 12,epidural extension in 28 and compression fracture in 14.Eleven patients underwent surgical decompression prior to the onset of RT.Median radiation dose was 24 Gy(range 8–30 Gy).Stereotactic radiation was delivered in 4 patients;33 patients received conformal RT.21 patients received PD-1 inhibition after RT,9 before RT and 7 with RT.Seven patients received concurrent CTLA-4 inhibitors with anti-PD-1 therapy. Treatment was in general well tolerated.Toxicities included fatigue(6),transient pain flare(1), nausea/vomiting(1)and G1 skin changes(1).All patients reported some degree of pain relief. Numbness/weakness was improved in 6 of 13 patients with baseline symptoms(46%)and this was more likely in patients that received vertebral radiation after starting PD-1 inhibitors (71% versus 17%, p=0.04). Most patients (22 of 33 evaluable patients, 67%) had stability of irradiated lesions on subsequent follow up imaging performed at median of 30 days from RT, whereas 3 had a complete local response and 4 had a partial local response. Conclusions: We demonstrate that PRT administered to vertebral metastases was well tolerated and effective in patients treated with PD-1 inhibitors. There was an encouraging rate of pain reduction and neurological improvement compared to historical series.